2017
DOI: 10.1515/cpp-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Review paper. Gluten-related disorders and schizophrenia - potential linking mechanisms, diagnostic and therapeutic challenge

Abstract: More and more evidence confirms the theory that the intake of cereal products containing gluten may play an important role in the pathogenesis of many diseases. There are also premises indicating the relationship between the so-called gluten-related diseases and the development and course of mental disorders, including schizophrenia.The aim of this article is to review the literature on the potential relationship between the consumption of gluten and schizophrenia, considering the etiopathogenesis and the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
(268 reference statements)
0
3
0
1
Order By: Relevance
“…Another treatable immune model of schizophrenia is gluten sensitivity with the occurrence of anti-tissue transglutaminase or anti-gliadin antibodies [ 94 ]. Indeed, there can be a possible relationship between diet rich in grain products with high gluten content and the occurrence or exacerbation of schizophrenia symptoms [ 95 ].…”
Section: Schizophrenia As a Complex Diseasementioning
confidence: 99%
“…Another treatable immune model of schizophrenia is gluten sensitivity with the occurrence of anti-tissue transglutaminase or anti-gliadin antibodies [ 94 ]. Indeed, there can be a possible relationship between diet rich in grain products with high gluten content and the occurrence or exacerbation of schizophrenia symptoms [ 95 ].…”
Section: Schizophrenia As a Complex Diseasementioning
confidence: 99%
“…Elevated Anti-Gliadin antibodies (AGA) are more frequent in people with schizophrenia than people without, and AGA has been positively associated with peripheral inflammatory markers ( Kelly et al., 2018 ) in people with schizophrenia. Case reports in human subjects with elevated AGA have suggested improvements in symptomatology following a gluten-free diet ( Tomaka et al., 2017 ), however similar to the ketogenic diet, there is a paucity of RCTs and therefore a lack of evidence for cause and effect.…”
Section: Pathwaysmentioning
confidence: 99%
“…The lowest incidence is 4%, the highest incidence is 29%, and there is a great connection between body weight and constipation [38] . Studies have confirmed that the intake of gluten containing cereal products plays an Published by Francis Academic Press, UK -62-important role in the pathogenesis of schizophrenia, and considering its pathogenesis, the treatment methods of schizophrenia were analyzed [39] . At the same time, Brazilian scholars have reported that unhealthy food may be related to constipation in dietary analysis, and finally concluded that poor eating habits such as insufficient intake of vegetables and fruits are significantly positively correlated with constipation [40] .…”
Section: Discussionmentioning
confidence: 99%